노인 대상 라이프스타일 관련 작업치료 중재프로그램의 구성요소 도출 : 델파이 조사를 바탕으로 - 신윤찬; 박다솔; 조은혜; 원경아; 한대성; 김정란 (대한작업치료학회지, 2020)
목적 : 노인을 대상으로 포괄적으로 사용되고 있는 개념인 라이프스타일에 접근하기 위해, 관련 중재프로그램의 구성요소를 도출하여 프로그램 구성 시 사용될 수 있는 근거 자료를 제공하려한다. 연구방법 : 지역사회 및 노인과 관련된 전문가 패널 12명을 대상으로 2018년 11월부터 12월까지 델파이조사를 3회 실시하였다. 1차에서는 노인 대상 라이프스타일 관련 중재프로그램에 대한 선행연구들을 종합 분석한 후, 구성요소에 관한 폐쇄형 항목 및 서술형 응답칸을 사용하여 의견을 수집하였다. 2차, 3차에서는 구성요소의 적합도와 중요도를 알아보았고, 도출된 결과를 토대로 ‘노인 대상 라이프스타일 관련중재프로그램의 구성요소’를 도출하였다. 결과 : 1차 델파이 결과, 선행연구 분석을 통해 제시된 37개 항목에서 삭제되거나 수정되어 23개의 구성요소가 선정되었고, 2차 델파이 결과에서는 50개의 구성요소가 합의되었다. 최종 3차 델파이 조사를 통해서는 22개의 항목이 선정되었으며, 최종 선정된 항목에 대한 내용타당도 비율은 0.77, 안정도는 0.20으로 확인되었다. 결론 : 본 연구를 통해 도출된 노인의 라이프스타일 관련 중재프로그램의 구성요소는 지역사회 기반을 포함한 다양한 임상 현장에서 효율적인 라이프스타일 중재를 계획 및 시행하는데 근거자료로써 활용될 수있을 것이다. Objective: To approach the comprehensive concept of lifestyle used for the elderly, the purpose of this study is toprovide baseline data that can be used to plan a lifestyle-related intervention program by deriving the variouscomponents. Methods: Delphi surveys were conducted three times from November to December 2018 by 12 expert panelsrelated to the community and the elderly. We analyzed previous studies on a lifestyle-related interventionprogram for the elderly, and in the first survey, opinions were gathered through the items reconstructed usingclosed-ended and open-ended questions for the components of a lifestyle-related intervention program. In thesecond and third surveys, we determined the fitness and importance of each component and derived thecomponents of a lifestyle-related intervention program for the elderly based on the results. Results: A total of 37 items were selected through an analysis of previous research, and some items were deletedor newly added from the first Delphi, with 51 items finally being selected. In the second survey, 50 componentswere selected as appropriate. In the final Delphi survey, 22 items were agreed upon as being appropriate, and theaverage content validity ratio for the final item was 0.77 and the stability was 0.20. Conclusions: The components of the lifestyle-related intervention program derived from this study can be used asa basis for planning and implementing effective lifestyle interventions in various clinical settings, includingcommunity settings. KCI Citation Count: 4